Greenhouse gas emission budgets and policies for zero-carbon road transport in Europe - Patrick Plötz; Jakob Wachsmuth; Frances Sprei; Till Gnann; Daniel Speth; Felix Neuner; Steffen Link (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2023)
Following the Paris Agreement, virtually all countries worldwide have committed themselves to undertaking efforts to limit global warming to 1.5êC. Within the European Union (EU), the recent "Fit for 55" policy package proposes ambitious greenhouse gas (GHG) mitigation policies for all sectors as part of the EU's contribution to limiting global warming. Yet, it is unclear whether the proposed policies are sufficient for the EU to limit global warming to 1.5êC and it remains an open policy problem how to translate global temperature targets into sector-specific emission budgets and further into sector-specific policies. Here, we derive GHG budgets for transport in EU27 and obtain GHG mitigation pathways for Europe consistent with 1.5êC global warming. We do not provide a comprehensive assessment of the "Fit for 55" transport package but we discuss the main policies for road transport in light of the GHG emission budgets, their level of ambition, and suggest amendments to these policies as well as improvements to the "Fit for 55" package. Our results suggest that parts of the "Fit for 55" for transport are still not ambitious enough to align with a 1.5êC scenario.
Keywords: 330; Climate policy; transport emissions; battery electric vehicles